1985
DOI: 10.1103/revmodphys.57.105
|View full text |Cite
|
Sign up to set email alerts
|

Crystals for quartz resonators

Abstract: This paper briefly describes the hydrothermal growth process and then discusses the important defects in quartz (twins, inclusions, dislocations, and impurities) and the correlations among them. The properties of quartz are reviewed and tabulated under the headings of intrinsic properties and defect-related properties. Resonator theory and fabrication techniques are outlined, with particular reference to aspects related to defects in the crystals. At this stage, it is possible to list the circuit design factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
80
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(83 citation statements)
references
References 66 publications
2
80
0
1
Order By: Relevance
“…This conclusion results from a set of selected articles, which includes the measurement of the frequency stability [WW75,RGBG00] and the interpretation of the flicker noise of crystal resonators [Kro98,Kro05]; the design fundamentals of the nowadays BVA resonators [Bes77]; some pioneering works on the low-frequency noise in quartz oscillators [BOM75,Dri75]; more recent articles focusing on specific design solutions for ultra-stable oscillators [Nor91, Nor96, CCG + 98, CCL + 03, TJA97]; and, as a complement, a thorough review of the SiO 2 crystal for the resonator fabrication is found in [Bri85]. Conversely, in everyday-life oscillators, which span from the low-cost XOs to the OCXOs used in telecommunications and instrumentation, the relative simplicity of the low-noise electronics required indicates that the frequency flicker is chiefly the 1/f fluctuation of the resonator.…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion results from a set of selected articles, which includes the measurement of the frequency stability [WW75,RGBG00] and the interpretation of the flicker noise of crystal resonators [Kro98,Kro05]; the design fundamentals of the nowadays BVA resonators [Bes77]; some pioneering works on the low-frequency noise in quartz oscillators [BOM75,Dri75]; more recent articles focusing on specific design solutions for ultra-stable oscillators [Nor91, Nor96, CCG + 98, CCL + 03, TJA97]; and, as a complement, a thorough review of the SiO 2 crystal for the resonator fabrication is found in [Bri85]. Conversely, in everyday-life oscillators, which span from the low-cost XOs to the OCXOs used in telecommunications and instrumentation, the relative simplicity of the low-noise electronics required indicates that the frequency flicker is chiefly the 1/f fluctuation of the resonator.…”
Section: Introductionmentioning
confidence: 99%
“…This expands the possibility of the use of the frequency stable quartz crystal oscillator by influencing quartz crystal equivalent circuit as a capacitive transducer whose capacitance is in the range 4−8 pF. Stable oscillation and high sensitivity in this range [6,[37][38][39][40][41] are thus one of this method's major advantages.…”
Section: Reactance-to-frequency Transducer Circuitmentioning
confidence: 99%
“…The data of the electrical quartz crystals' equivalent elements are f 0 = 4 MHz, R = 10 Ohm, C = 25 fF, L = 64 mH, C o = 4 pF, quality Q = 80 k. The frequency f 0 was selected due to a greater oscillation amplitude and a higher Q value for the selected oscillation circuit. The new method (Figure 3) allows the AT-cut crystal temperature characteristics compensation (under 0.02 Hz) in the above temperature range through the switching circuit compensating this characteristics and reducing its influence to a minimum [22,37,42].…”
Section: Frequency Stability Of the Transducermentioning
confidence: 99%
“…Apart from the intrinsic quality of the crystals (inclusions, impurities, dislocations, etc.) [1], the nature of the vibration pattern is an important characteristic of such resonators [2], which directly affects their performance. Although there exist numerous methods for visualising the standing wave patterns in these crystals, all of these methods are indirect in nature and suffer from different limitations.…”
Section: Introductionmentioning
confidence: 99%